Subsidy or market reform? Rethinking China's farm consolidation strategy. (November 2015) - Rada, Nicholas; Wang, Chenggang; Qin, Lijian
Highlights: We analyze farm-size expansion in China using a national farm-household sample. We question whether grain yields and per-hectare net returns increase with farm size. Results suggest regional opportunities to increase grain farm sizes. Reducing farmland transaction costs may encourage the desired consolidation. Abstract: Chinese food security policy is anchored increasingly on the conviction that domestic grain production should be greatly enhanced, and the best way to do so is to expand farm production scale. To that end, an increasing stream of public investment has been directed to the grain sector, in the form for example of farm expansion subsidies. Our purpose is to assess the potential impacts of China's farm-scale expansion on both yields and per-hectare economic returns. Analysis of a large sample of farm household production data finds (with some exceptions) that grain yields likely will decline as farm size grows, compromising food self-sufficiency targets. More importantly, in only isolated cases would per-hectare economic returns decline with size. Thus, an emphasis on reducing farmland transactions costs may stimulate cropland consolidation and achieve the desired long-term structural transformation.